Conceptualizations of Domestic Violence–Related Needs among Women Who Resettled to the United States as Refugees. (29th August 2019) - Wachter, Karin; Dalpe, Jessica; Heffron, Laurie Cook
Abstract: Despite robust evidence of the myriad consequences associated with intimate partner violence (IPV), social services in the United States may not adequately account for and respond to variations in how women resettling as refugees conceptualize service and support needs. With this study, the authors sought to develop a more nuanced understanding of needs as expressed by women resettling to the United States as refugees. Researchers conducted in-depth interviews and focus groups with refugee women who resettled to the United States ( n  = 35) and social services providers ( n = 53), including those working in refugee resettlement or domestic violence agencies or community-based organizations. The research team used structural coding and thematic analysis to examine the data, through which they identified four themes: (1) living with enduring consequences of IPV, (2) "I just want them to help me, " (3) "I need you to talk to my husband, " and (4) "How will I pay the rent?" The study findings point to broader structural concerns shaping women's resettlement experiences, as well as areas of incongruence between women's conceptualizations of needs and established practice approaches. Implications for culturally competent and survivor-centered practice are discussed.